2007
DOI: 10.1016/j.nurt.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Talampanel

Abstract: Summary:Talampanel is a novel anticonvulsant that acts as an allosteric inhibitor of the AMPA receptor. Talampanel has a broad spectrum of action in animal models of epilepsy and neuroprotection. Clinical experience to date has been able to show effectiveness in reduction of seizures in patients with refractory partial seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 21 publications
1
52
0
2
Order By: Relevance
“…Indeed, AMPA receptor antagonists have shown efficacy in animal models of cerebral ischemia and in seizure reduction in clinical trials (49). By analogy, compounds that antagonize the interaction between TARPs and AMPA receptors should down-regulate strong depolarizing responses and could be useful in excitotoxic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, AMPA receptor antagonists have shown efficacy in animal models of cerebral ischemia and in seizure reduction in clinical trials (49). By analogy, compounds that antagonize the interaction between TARPs and AMPA receptors should down-regulate strong depolarizing responses and could be useful in excitotoxic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Talampanel (GYKI 53773, LY300164; Howes and Bell, 2007) and perampanel (E2007) are noncompetitive antagonists that are highly selective for AMPA over other glutamate receptors. Talampanel demonstrated efficacy in phase II trials in patients with refractory partial seizures (Chappell et al, 2002), and perampanel is under study.…”
Section: B the Next Generation ␣-Amino-3-hydroxy-5-methyl-4-isoxazolmentioning
confidence: 99%
“…Moreover, the anticonvulsant effects of compound 6d were comparable to those of active 2,3-benzodiazepine derivatives CFM-2 and talampanel, which has already undergone phase 1 and 2 trials for refractory epilepsy, as well as amyotrophic lateral sclerosis and Parkinson disease. 21,22) It is interesting to note that in this experimental model of epilepsy the observed activity of compound 6d exceeded that of valproate and gabapentin, two drugs largely used in antiepileptic therapy. On the basis of calculation of Log D 7.4 , 26) predicted from a commercially available program (advanced chemistry development/Lab), we hypothesized that the hydrophobic character of methyl substituent could positively contribute to the blood-brain barrier crossing thus improving the anticonvulsant efficacy.…”
Section: Resultsmentioning
confidence: 84%
“…1). 17,21,22) Starting from the "lead compound" 1, in several previous studies, we examined a large series of its analogues and reported a comprehensive structure-active relationship (SAR) studies concerning the influence of specific substituents on tetrahydroisoquinoline skeleton; we found that the most active derivatives are generally characterized by the presence of 2-acetyl substituent; moreover two methoxy substituents on the benzene fused ring are crucial to produce pharmacological effects.19) Furthermore our investigations suggested that the introduction of hydrophobic substituents at 4Ј-position of C-1 phenyl moiety (e.g. halogen atoms) could improve the anticonvulsant efficacy against sound-induced seizures in Dilute Brown non-Agouti (DBA/2) mice.…”
mentioning
confidence: 99%